Intensity of Religious Moderation According to the Medina Constitution - Arlis; Hidayat, Rahmat; Ahmad Bakhtiar Jelani (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2022)
This study aimed to examine the intensity of concept and practice of religious moderation according to the Constitution of Medina. There is a gap between the divine constitution as an ideal guide to religious moderation and the regulation and practice of religious moderation in various countries. So it is very important to have a comprehensive understanding of the concepts and practices of religious moderation according to the constitution of medina. Study use normative Islamic legal research methods with primary legal materials as the main data. The approach used is semantic aproach and the concept of legal intensity. The result of the study was that the intensity of religious moderation based on the constitution of medina is very strong, great and is at the highest degree which includes aspects of believe, sharia, and morals. Based on the analysis of the data it was found that there are several concepts that mean moderation in the material of the translated content, hadith, and constitution of Medina. The concept is use of the word best, currently, mid, fair, choice, and moderate. Manifestation of moderation in the mission objectives of the Prophet, in the field of faith, in the treatment of human error, in the rights and duties of the physical and family, in the gathering of the good of the world and the hereafter, in communicating with culture, and manifestation of moderation in dealing with others. The intensity of religious moderation according to the constitution of medina is called qur’ani moderation. Keywords: Intensity; Religious Moderation; Madinah Constitution